In the Model Cell Lines of Moderately and Poorly Differentiated Endometrial Carcinoma, Estrogens Can Be Formed via the Sulfatase Pathway - Pavlič, Renata; Gjorgoska, Marija; Hafner, Eva; Sinreih, Maša; Gajser, Kristina; Poschner, Stefan; Jäger, Walter; Rižner, Tea Lanišnik (Frontiers in Molecular Biosciences, 2021)
Endometrial cancer (EC) is the most common gynecological malignancy in resource-abundant countries. The majority of EC cases are estrogen dependent but the mechanisms of estrogen biosynthesis and oxidative metabolism and estrogen action are not completely understood. Here, we evaluated formation of estrogens in models of moderately and poorly differentiated EC: RL95-2 and KLE cells, respectively. Results revealed high expression of estrone-sulfate (E1-S) transporters (SLCO1A2, SLCO1B3, SLCO1C1, SLCO3A1, SLC10A6, SLC22A9), and increased E1-S uptake in KLE versus RL95-2 cells. In RL95-2 cells, higher levels of sulfatase and better metabolism of E1-S to E1 were confirmed compared to KLE cells. In KLE cells, disturbed balance in expression of HSD17B genes led to enhanced activation of E1 to E2, compared to RL95-2 cells. Additionally, increased CYP1B1 expression and down-regulation of genes encoding phase II metabolic enzymes: COMT, NQO1, NQO2, and GSTP1 suggested decreased detoxification of carcinogenic metabolites in KLE cells. Results indicate that in model cell lines of moderately and poorly differentiated EC, estrogens can be formed via the sulfatase pathway.